Microstructure, mechanical properties and cutting performance of sintered sub-micron WC-Co hardmetal powder - Mohd Asri, Selamat; S.A., Manaf; Talib Ria, Jaafar (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.